The Elimination of Constitutional Court's Authority in The Dispute Case of General Election of Regional Head (Analysis of Decision of the Constitutional Court Number 97/PUU-XI/2013) - Jentel Chairnosia (Jurnal Cita Hukum, 2017)
The enactment of Law Number 32 Year 2004 is a manifestation of the development ofadvanced democracy, namely all local chief elected directly by the people except the positionof the Governor of Yogyakarta. However, in its development, the implementation of theGeneral Elections of Regional Head gave rise to dissatisfaction which resulted in the appealof the results of the General Election to the court for various reasons. The presence of theConstitutional Court as an institution that resolved the dispute over the General Election ofRegional Heads has not been able to provide justice to the public, especially the emergenceof many Constitutional Court rulings that cause debate. In its development, the ConstitutionalCourt abolished its authority in the settlement of disputes in the General Election of RegionalHeads as stipulated in Decision Number 97 / PUU-XI / 2013. The Constitutional Court is ofthe opinion that the Constitutional Court only has the authority to resolve election disputes ofDPR, DPD, President/Vice President because the election is done nationally, while theelection is conducted in certain areas only. In addition, the volume of incoming cases relatedto election disputes more than the law review case which is the main authority of theConstitutional Court, so that this can affect the quality of the decisions of the ConstitutionalCourt considering the dispute resolution of the results of the General Election should beterminated within fourteen days. DOI: 10.15408/jch.v5i2.7090